MODERN TRANSFORMATION OF THE RUSSIAN ECONOMY - O. Pakova; J. Konopleva; M. Babenko; E. Pasko; B. Vakhidov (Вестник Северо-Кавказского федерального университета)
This research focuses on the study of the features of the transformation of the modern configuratn of the Russian economy from a simple market to a digital one. The article examines certain points and factors associated with the transformation, given an assessment of the activities ofplatform organizations, the influence of innovations on the standard of living of population substantiated, specific examples are given that symbolize the transition of our economy to new realities. We also analyzed the possibility of development in the near future of financial technology industry, in particular its elements, such as neobanks and the «blockchain» technology.